Impact of Strategic Planning on Organizational Performance and Survival of Nepalese Commercial Banks - Yadav, Prabesh Kumar (Nepalese Journal of Finance, 2024)
This study investigates the impact of strategic planning on organizational performance and survival of Nepalese commercial banks. Organizational performance is the dependent variable. The selected independent variables are organizational structure, environmental scanning, strategy implementation, strategy formulation, strategy evaluation and control. The primary source of data is used to assess the opinions of the respondents regarding the strategic planning and its impact on survival and performance of commercial banks in Nepal. The study is based on primary data of 16 commercial banks with 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of strategic planning on performance and survival of Nepalese commercial banks. The study showed that organizational structure has a positive impact on organizational performance. It indicates that better organizational structure is associated with sound performance and survival of banks. Similarly, environmental scanning has a positive impact on organizational performance. It implies that prior environmental scanning stimulates the organizational performance. Similarly, strategy implementation has a positive impact on organizational performance. It reveals that proper strategy implementation drives the organizational performance. The study also showed that strategy formulation has a positive impact on organizational performance. It indicates that feasible and suitable strategy formulation stimulates the organizational performance. Furthermore, strategy evaluation and control has positive impact on organizational performance. It indicates that proper and on time strategy evaluation and control drives the organizational performance.